(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article is a synthesis view of the aristocratic characters in Azerbaijani drama. Raised in that period dramas problems were brought to the fore. Environment in which they were established drama, the reason for their writing, some were involved in the study. General directions were given to other researchers. Have to note, as in the dramatic art of the period about which it is told, along with the inconsistent moments, it is a lot of and similar, even repeating plots. The main line causing similarity of drama works, the appeal in everyone to education and a saturation critical ideas concerning ignorance, nonsense is. The author comes to a conclusion that falling into the decline, the decaying pomeshchichestvo needs reforms. It will be carried out by the intelligent people being heralds of progressive idea